ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP KINERJA KARYAWAN MELALUI MEDIASI MOTIVASI KARYAWAN PADA KARYAWAN INDUSTRI MANUFAKTURING DI BATAM - Nelson, Alden; Lim, Jevie; Setyawan, Agustinus (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
This study aims to determine the effect of the independent variable Job Characteristics on the dependent variable Employee Performance by using the Employee Motivation variable as a mediating variable. The respondent is from employees in the manufacturing industry in Panbil Industrial Estate. The method used in this research is a survey method by distributing 250 questionnaires. There are 236 questionnaires from 250 questionnaires distributed to employees who have been filled in, and the collected data tested using the Smart PLS. The data test results identify that there is a significant relationship to all variables so that all hypotheses can also be accepted. This study also recommends that companies consider the job characteristics of employees more in order to increase employee motivation so that it can produce maximum employee performance and achieve company targets.